New Naphthyl Substituted Phytosterol and Lanostane Type-triterpenic Esters from the Stem Bark of Ficus religiosa L. - Ali, Abuzer; Jameel, Mohammad; Ali, Mohammed (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Ficus religiosa L. (Moraceae) is considered as a holy tree in most of the part of south-eastern Asia. Traditionally, its bark is used in the treatment of burns, diarrhoea, dysentery, gastrohelcosis and gonorrhoea, glandular swellings of the neck, scabies, piles, urogenital disorders, anxiety, vomiting, skin diseases and prescribed to improve the skin complexion. Materials and Methods: The methanol extract of stem bark of F. religiosa was obtained by continuous hot extraction process. Isolation of phytoconstituents was done by silica gel column chromatography. Analytical thin layer chromatography was used to check the homogeneity of eluted fractions. The structures of isolated compounds were established on the basis of 1D and 2D NMR, FT-IR, UV and MS data and chemical means. Results: Phytochemical investigation of the methanol extract of F. religiosa stem bark led to the isolation of a new naphthyl substituted phytosterol characterized as naphthyl-1ʹ,3ʹ-diol-1ʹ-3β-sitosteryl-3ʹ-linoleinate (1) and a new lanostane type-triterpenic ester elucidated as lanostan-19-oic acid-3β-olyl-oleate (2). Conclusion: The present work has enhanced the phytochemical profile of F. religiosa. Compound 1 and 2 have been isolated for the first time from this plant and might be used as chromatographic markers for the quality control analysis of its marketed herbal formulations.
Keywords: Ficus religiosa; Stem bark; Phytosterol ester; Lanostanol ester; Isolation; characterization; β-sitosteryl naphthadiolyl linoleinate; Lanostanoic acid oleate